Genotype effects of cowpea and soybean on nodulation, N2-fixation and N-balance in the Northern Guinea Savanna of Nigeria - Yusuf, A. A.; Abaidoo, R. C.; Iwuafor, E.N.O.; Olufajo, O. O. (Journal of Agronomy, 2016)
An article published by Journal of Agronomy 7(3): 258-264, 2008